Korelasi Hasil Pemeriksaan Mikroskopis Sputum Basil Tahan Asam dengan Tes Cepat Molekuler (GeneXpert) pada Pasien Tuberkulosis di RSUD dr. Loekmono Hadi Kudus - Aini Rizka Amalia Zamroni; Yunita Rusidah; Anisa Sholikhati (Poltekkes Kemenkes Semarang, 2025)
Tuberculosis (TB) remains a leading cause of global mortality, with 10.6 million new cases reported worldwide in 2023 by the World Health Organization (WHO), including 450,000 cases of rifampicin-resistant TB (RR-TB). This study aimed to determine the correlation between Acid-Fast Bacilli (AFB) smear and Rapid Molecular Test (TCM) results among TB patients at Dr. Loekmono Hadi General Hospital, Kudus. This descriptive-analytic study employed a cross-sectional design and involved 45 randomly selected TB patients who met the inclusion and exclusion criteria in January 2025. Each patient underwent both AFB smear and TCM (GeneXpert) examinations. Data were analyzed using univariate and bivariate analysis, with the Chi-Square test used to assess the correlation. The results showed that the majority of patients were aged 46–65 years (48.8%) and male (57.8%). TCM detected MTB Not Detected in 66.7% of patients, while 80% had negative AFB smear results. The Chi-Square test revealed a significant correlation between the two methods (p < 0.001). In conclusion, TCM is more sensitive than AFB smear in detecting TB. These findings imply that broader implementation of TCM in TB screening and diagnosis is essential to enhance early detection accuracy and improve disease control efforts.